Голубая змейка: Уральские сказы / П. П. Бажов - Бажов Павел Петрович (Внеклассное чтение, 2017)
Экземпляры: 6 () / Инвентарный номер: 50454 / Цена: 56.00 / Авт.знак: Б 16 / ГРНТИ: 17.82.93 / ББК: 84(2=411.2)6